Bangladesh Model/Survey Note : Assessment of Implementation of Public Procurement Regulations - World Bank (Washington, DC, 2013)
The report provides an assessment of the status of implementation of public procurement regulations 2003. The objective was to assess the performance of the system using a two-way approach. The report summarizes the major findings of the assessment carried out through a Bank-Government joint collaboration survey with sample data of two financial years (FY2006 and FY2007) from the key sectoral ministries/agencies including the Roads and Highways Department (RHD), Local Government Engineering Department (LGED), Rural Electrification Board (REB), and Bangladesh Water Development Board (BWDB). Although Bangladesh has made good progress in establishing the foundations for an effective public procurement system by introducing necessary legislations and regulatory institutions, the results of this assessment show that overall the system has been performing poor to average. The performance is poor as regards efficiency of procurement process and contract management, and it is average in terms of competitiveness and transparency. Procurement delays are a major challenge, affecting project implementation. The higher the level of contract approving authority, the lesser is the efficiency of the procurement system. Though important strides have been made in changing the procurement environment, yet its application has proven to be relatively inconsistent.